Plan estratégico para la empresa publicitaria rótulos y artes “el gato” del cantón la Joya de los Sachas, provincia de Orellana para el periodo 2015-2019 - Piaguaje Piaguaje, Benigno Raúl (2015)
The advertising company Signs and Arts "CAT", since its inception has been dedicated to advertising service as graphic design and production of all kinds of promotional products, today constantly faces major competitors and changes in the economic sector due to the progress of society, for that reason we have seen the need to establish a good strategic planning that allows them to define their priorities and objectives in the short and medium term. This research work focuses on developing a strategic plan, which is based mainly on raising key strategies to ensure compliance with the objectives; the development of research work, a diagnosis of the current situation of the company was conducted by applying strategic planning tools such as the SWOT matrix and analysis of the five forces porter, reaching establish their internal and external factors influencing the company. For the meeting of both general objectives and specific it split with the analysis of internal factors through the advertising company Signs and Arts "CAT" as well as external factors were investigated to its customers allowing realize their strengths, weaknesses, opportunities and threats. So that by the diagnosis could be identified shortcomings in the company and in the back were considered to strategize; which served for the elaboration of a proposed strategic plan for the Arts Signs and advertising company "CAT" for the period 2015-2019, the various development axes determined: corporate image, improving production processes, staff training, administrative management and service expansion. With these axes of development is to somehow help with alternative solutions to deficiencies in the company, allowing the strengthening and development to achieve their organizational goals and objectives. Later the programming matrix was obtained, then the operating plan and the proposal for a manual of functions allowing the development to each of the workers their activities in the best way was developed. Finally, they raise the respective conclusions and recommendations will be taken into account by the owner manager, for the improvement and development of the company.